2010
DOI: 10.1016/j.chemosphere.2009.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of fipronil in Óleo Lagoon in Jataí Ecological Station, São Paulo-Brazil

Abstract: Fipronil is a phenylpyrazole pesticide widely used to protect sugar-cane crops from insect pests. After reaching the environment, this insecticide may have several fates. This research aimed to propose a kinetic model to describe the fate of commercial fipronil Regent 800WG in the sediment-water interface of the Oleo Lagoon in the Mogi-Guaçu river floodplain, situated within the Jataí Ecological Station, by means of a microcosm scale experiment. Results showed that a small fraction of the pesticide is quickly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…In northwest São Paulo, the principal crop is sugarcane, and the cultivated area has increased in recent years (UNICA, 2015). Sugarcane cultivation requires a large amount of pesticides, especially the herbicides diuron, tebuthiuron and glyphosate and the insecticides carbofuran and fipronil (Bicalho et al, 2010;Peret et al, 2010). In Brazil and other tropical regions of the world, application of these pesticides is generally intensified during the rainy season, which coincides with the reproductive period of most amphibian species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In northwest São Paulo, the principal crop is sugarcane, and the cultivated area has increased in recent years (UNICA, 2015). Sugarcane cultivation requires a large amount of pesticides, especially the herbicides diuron, tebuthiuron and glyphosate and the insecticides carbofuran and fipronil (Bicalho et al, 2010;Peret et al, 2010). In Brazil and other tropical regions of the world, application of these pesticides is generally intensified during the rainy season, which coincides with the reproductive period of most amphibian species.…”
Section: Introductionmentioning
confidence: 99%
“…In general, pesticides may be transported by drift, precipitation and runoff and may be found in different environmental matrices such as soil, surface water, and sediment, thus affecting various non-target organisms (Edwards, 1993;Hoerger et al, 2014;LeNoir et al, 1999;Moreira et al, 2010;Peret et al, 2010;Rand et al, 1995). Once in the environment, pesticides can be degraded, generating by-products that can be more or less toxic than the original compound (Cheyns et al, 2010;Gunasekara and Troung, 2007;Katagi, 2004;Muneer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is unstable in the environment because it is affected by UV radiation (Mianjy and Niknafs, 2013), pH (Ramesh and Balasubramanian, 1999) and temperature (Ma et al, 2012). It is biodegradable (Peret et al, 2010;Hussain et al, 2016), and some of its transformation products show enhanced toxicity against non-target organisms compared to the parent compound (Michel et al, 2016). Reports have indicated that temperature influences the toxicity of insecticides on target organisms (Ma et al, 2012), although the effects are irregular.…”
Section: Introductionmentioning
confidence: 99%
“…The rise in fipronil consumption may be due to its effectiveness against insects that are resistant to pyrethroids, organophosphate and carbamate insecticides. After reaching the environment, this insecticide may have several fates as water, soil and biota [7].…”
Section: Introductionmentioning
confidence: 99%